Electroencephalogram Mechanism of Dexmedetomidine Deepening Sevoflurane Anesthesia - Zhang, Lei; Li, Hua; Deng, Liyun; Fang, Kun; Cao, Yuanyuan; Huang, Cheng; Gu, Erwei; Li, Jun (Frontiers in Neuroscience, 2022)
Dexmedetomidine, as an α2-adrenoceptor agonist, plays anti-sympathetic, sedative and analgesic roles in perioperative period. Also, dexmedetomidine can reduce the minimal alveolar concentration (MAC) of sevoflurane and the risk of postoperative cognitive dysfunction during sevoflurane anesthesia. But so far, the electroencephalogram (EEG) mechanism of dexmedetomidine deepening sevoflurane anesthesia is not clear. In this study, by analyzing the changes of the bicoherence of EEG before and after dexmedetomidine infusion, the EEG mechanism of dexmedetomidine on sevoflurane anesthesia effect was studied. We analysed dexmedetomidine-induced changes in bicoherence in 23 patients under sevoflurane anesthesia. After anesthesia induction, the sevoflurane concentration was maintained at 0.8 MAC; a loading dexmedetomidine dose of 0.8 μg/kg was injected, followed by a maintenance dose of 0.5 μg•kg-1h-1 10 min later. Frontal EEG data from 5 min before and 10 min after dexmedetomidine infusion were compared using the Wilcoxon signed-rank and paired t tests. After dexmedetomidine infusion, the median θ bicoherence peak increased from 29.71% to 43.42% and shifted to a lower frequency. The α bicoherence peak increased from 41.49% to 46.36% and shifted to a lower frequency. The α power peak decreased from 5.88 to 5.17 dB and shifted to a lower frequency. These results demonstrate that dexmedetomidine deepen sevoflurane anesthesia by enhancing α and θ bicoherence and shifting peak values of these bands to lower frequencies.